Lipid Profile in Confirmed Covid-19 Patients with Type 2 Diabetes Mellitus At Haji Adam Malik General Hospital Medan from March 2020 to December 2021 - Sitepu, Annisa Nidya Rahmatika; Lindarto, Dharma; Nasution, Melati Silvanni (CoinReads Media Prima, 2023)
Introduction: Diabetes can cause secondary hyperlipidemia. In COVID-19, dyslipidemia is thought to be the result of biological and pathological processes triggered by SARS-CoV-2. Altered lipid profiles have been reported since the beginning of the COVID-19 pandemic, where the alteration of lipid profile and the severity of SARS-CoV-2 infection were positively correlated. This study aims to analyze the lipid profile in confirmed COVID-19 patients with T2DM at H. Adam Malik General Hospital Medan. Method: This was a descriptive study with a cross-sectional design using a total sampling technique by collecting secondary data on inpatients with confirmed COVID-19 with T2DM at H. Adam Malik General Hospital from 2020 to 2021 which was then analyzed using the SPSS version 25 application. Results: Of the 372 subjects, the most common sex was male (57.3%), 193 people had a BMI of 18.5 - 24.9kg/m2 (51.9%), the mean overall age was 57.5 ± 10.4 years, and the median length of stay was 8 days. The most common comorbid was hypertension (n=189, 50.8%), 176 people had severe COVID-19 (47.3%), and 225 patients were discharged (60.5%). Based on laboratory data, 327 people had dyslipidemia (87.9%), 31 people had mild acute liver impairments (8.3%), the average of HbA1c was 9.0±2.5%, the average fasting blood glucose was 221.7±122.2 mg/L, the average 2 hours post-prandial blood glucose was 261.7±125.8 mg/L, an average of total cholesterol was 151.2±52.2 mg/L, an average of triglycerides was 147.5±99.1 mg/L, an average of HDL was 33.1±14.6 mg/L, an average of LDL was 97.4±44.5 mg/L, the median of ALT was 25 μ/L, and an average of AST was 30.45±27.42 μ/L. Conclusion: Total cholesterol, triglyceride, and LDL were lower in T2DM patients with a critical illness of COVID-19 and patients who died.